Electrochemical reactivity of Ponceau 4R (food additive E124) in different electrolytes and batch cells. (10th August 2015) - Thiam, Abdoulaye; Brillas, Enric; Centellas, Francesc; Cabot, Pere L.; Sirés, Ignasi
Highlights: Food color additive Ponceau 4R treated by electrochemical advanced oxidation processes. Faster decolorization in the order SO4 2− ∼ ClO4 − < NO3 − << Cl − . Faster mineralization in the order Cl − << SO4 2− ∼ ClO4 − < NO3 − . Generation of oxychlorine anions (ClO3 − and ClO4 − ) and active chlorine in Cl − medium. Photoelectro-Fenton process with a Pt or BDD anode exhibited the best performance. Abstract: The occurrence of food color additives in waters is becoming a hot topic due to their potential health effects, especially on children. The treatment of Ponceau 4R solutions by electro-oxidation (EO) with or without H2 O2 production, electro-Fenton (EF) and photoelectro-Fenton (PEF) using small undivided and divided batch cells with either Pt or BDD as the anode has been thoroughly studied. The electrolyses were performed in different electrolytes like Na2 SO4, NaCl, NaNO3 and LiClO4 in order to elucidate the changes in reactivity. Depending on the anode, cathode, process and electrolyte, the azo dye could be degraded due to the single or combined action of: (i) direct cathodic reduction and/or anodic oxidation, (ii) OH-mediated oxidation at the anode vicinity or in the solution bulk, and (iii) active chlorine-mediated oxidation. The presence of Cl − led to the fastest decolorization, whereas it became detrimental for total organic carbon abatement. The oxidation of Cl − to active chlorine (Cl2 and HClO) and oxychlorine anions (ClO3 − and ClO4 − ) by direct charge transfer or by M( OH) and OH was investigated. Color removal was much slower in SO4 2−, ClO4 − and NO3 − media, although the latter was particularly beneficial in PEF and/or using BDD. Regarding the mineralization, PEF outperformed the other technologies. Similar trends were observed in SO4 2− and ClO4 − media, being slightly favored in NO3 − . In contrast, Cl − medium tended to be detrimental due to the formation of refractory chloroderivatives, the destruction of M( OH) to form less oxidizing (oxy) chloro radicals, oxychlorine anions and active chlorine, and the reaction between HClO and H2 O2 . Experiments in divided cells demonstrated the very small contribution of cathodic reduction of the dye and its by-products. Linear sweep voltammetry revealed the direct oxidation of both, Ponceau 4R and Cl − on the anode surface.